Mutations in ASPRV1 Cause Dominantly Inherited Ichthyosis. - Boyden, Lynn M; Zhou, Jing; Hu, Ronghua; Zaki, Theodore; Loring, Erin; Scott, Jared; Traupe, Heiko; Paller, Amy S; Lifton, Richard P; Choate, Keith A (Am J Hum Genet, 2020)
The discovery of genetic causes of inherited skin disorders has been pivotal to the understanding of epidermal differentiation, function, and renewal. Here we show via exome sequencing that mutations in ASPRV1 (aspartic peptidase retroviral-like 1) cause a dominant Mendelian disorder featuring palmoplantar keratoderma and lamellar ichthyosis, a phenotype that has otherwise been exclusively recessive. ASPRV1 encodes a mammalian-specific and stratified epithelia-specific protease important in processing of filaggrin, a critical component of the uppermost epidermal layer. Three different heterozygous ASPRV1 missense mutations in four unrelated ichthyosis kindreds segregate with disease and disrupt protein residues within close proximity to each other and autocatalytic cleavage sites. Expression of mutant ASPRV1 proteins demonstrates that all three mutations alter ASPRV1 auto-cleavage and filaggrin processing, a function vital to epidermal barrier integrity.
Keywords: Aspartic Acid Endopeptidases; Heredity; Heterozygote; Humans; Ichthyosis, Lamellar; Intermediate Filament Proteins; Mutation, Missense; Phenotype; Skin Diseases; Whole Exome Sequencing

Mutations in KRT10 in epidermolytic acanthoma. - Cheraghlou, Shayan; Atzmony, Lihi; Roy, Simon F; McNiff, Jennifer M; Choate, Keith A (J Cutan Pathol, 2020)
BACKGROUND: Epidermolytic acanthoma (EA) is a rare acquired lesion demonstrating a characteristic histopathological pattern of epidermal degeneration referred to as epidermolytic hyperkeratosis (EHK). On histopathological analysis, EA appears nearly identical to inherited EHK-associated dermatoses such as epidermolytic ichthyosis and ichthyosis bullosa of Siemens. While it has been speculated that EA is caused by mutations in KRT10, KRT1, or KRT2 found in these inherited dermatoses, none have yet been identified. Herein, we aim to identify the contributions of keratin mutations to EA. METHODS: Using genomic DNA extracted from paraffin-embedded samples from departmental archives, we evaluated a discovery cohort using whole-exome sequencing (WES) and assessed remaining samples using Sanger sequencing screening and restriction fragment length polymorphism (RFLP) analysis. RESULTS: DNA from 16/20 cases in our sample was of sufficient quality for polymerase chain reaction amplification. WES of genomic DNA from lesional tissue revealed KRT10 c.466C > T, p.Arg156Cys mutations in 2/3 samples submitted for examination. RFLP analysis of these samples as well as eight additional samples confirmed the mutations identified via WES and identified four additional cases with Arg156 mutations. In sum, 6/11 screened cases showed hotspot mutation in KRT10. CONCLUSIONS: Hotspot mutations in the Arg156 position of KRT10, known to cause epidermolytic ichthyosis, also underlie EA.
Keywords: Acanthoma; Adult; Aged; Aged, 80 and over; Female; Genomics; Humans; Hyperkeratosis, Epidermolytic; Ichthyosis Bullosa of Siemens; Keratin-10; Keratins; Male; Middle Aged; Mutation; Skin Neoplasms; Whole Exome Sequencing

Post-zygotic ACTB mutations underlie congenital smooth muscle hamartomas. - Atzmony, Lihi; Ugwu, Nelson; Zaki, Theodore D; Antaya, Richard J; Choate, Keith A (J Cutan Pathol, 2020)
BACKGROUND: Congenital smooth muscle hamartomas (CSMHs) are benign lesions that share clinical and histopathological features with Becker nevus, a mosaic disorder associated with post-zygotic ACTB mutations. Given the clinical and histopathological overlap between CSMH and Becker nevus, we hypothesized that post-zygotic mutations in ACTB may underlie CSMH. METHODS: Direct sequencing of ACTB gene in affected and unaffected tissue isolated from one case of hemihypertrichosis and hemihypertrophy corresponding to giant segmental CSMH and hemihypertrophy. This was followed by direct sequencing with and without enrichment assay for hotspot ACTB mutations in affected tissue from 12 samples of isolated CSMH from unrelated individuals. RESULTS: In total we identified somatic missense ACTB mutations in 9 out of 13 CSMHs (69%). Mutations were either novel or previously reported in Becker nevi and Becker nevus syndrome. CONCLUSIONS: CSMHs result from post-zygotic ACTB mutations. This study proves that CSMHs and Becker nevi are nosologically related, and expand the phenotypic spectrum of ACTB mutations.

Topical cholesterol/lovastatin for the treatment of porokeratosis: A pathogenesis-directed therapy. - Atzmony, Lihi; Lim, Young H; Hamilton, Claire; Leventhal, Jonathan S; Wagner, Annette; Paller, Amy S; Choate, Keith A (J Am Acad Dermatol, 2020)
BACKGROUND: Porokeratosis is associated with mevalonate pathway gene mutations. Therapeutic options are few and often limited in efficacy. We hypothesized that topical therapy that aims to replenish cholesterol, an essential mevalonate pathway end-product, and block the accumulation of mevalonate pathway toxic metabolites could alleviate porokeratosis. OBJECTIVE: To study the efficacy of topical cholesterol/lovastatin in different variants of porokeratosis. METHODS: We enrolled a series of 5 porokeratosis patients,1 with disseminated superficial actinic porokeratosis, 2 with porokeratosis palmaris et plantaris disseminata, and 2 with linear porokeratosis. Patients were genotyped before initiation of therapy. Patients then applied topical cholesterol/lovastatin twice daily to a unilaterally defined treatment area for up to 3 months. The response was evaluated and patients photographed at every visit. RESULTS: Three patients had MVD mutations, and 2 patients had PMVK mutations. Treatment with topical cholesterol/lovastatin (but not cholesterol alone) resulted in near complete clearance of disseminated superficial actinic porokeratosis lesions after 4 weeks of therapy and moderate improvement of porokeratosis palmaris et plantaris disseminata lesions and linear porokeratosis lesions. There were no adverse events. LIMITATIONS: Case series design with a small number of patients. CONCLUSION: Topical cholesterol/lovastatin is an effective and well-tolerated therapy for porokeratosis that underscores the utility of a pathogenesis-based therapy that replaces deficient end products and prevents accumulation of potentially toxic precursors.

Two percent lovastatin ointment as a pathogenesis-directed monotherapy for porokeratosis. - Ugwu, Nelson; Choate, Keith A; Atzmony, Lihi (JAAD Case Rep, 2020)

Mutations in PERP Cause Dominant and Recessive Keratoderma. - Duchatelet, Sabine; Boyden, Lynn M; Ishida-Yamamoto, Akemi; Zhou, Jing; Guibbal, Laure; Hu, Ronghua; Lim, Young H; Bole-Feysot, Christine; Nitschké, Patrick; Santos-Simarro, Fernando; de Lucas, Raul; Milstone, Leonard M; et al. (J Invest Dermatol, 2019)
Investigation of genetic determinants of Mendelian skin disorders has substantially advanced understanding of epidermal biology. Here we show that mutations in PERP, encoding a crucial component of desmosomes, cause both dominant and recessive human keratoderma. Heterozygosity for a C-terminal truncation, which produces a protein that appears to be unstably incorporated into desmosomes, causes Olmsted syndrome with severe periorificial and palmoplantar keratoderma in multiple unrelated kindreds. Homozygosity for an N-terminal truncation ablates expression and causes widespread erythrokeratoderma, with expansion of epidermal differentiation markers. Both exhibit epidermal hyperproliferation, immature desmosomes lacking a dense midline observed via electron microscopy, and impaired intercellular adhesion upon mechanical stress. Localization of other desmosomal components appears normal, which is in contrast to other conditions caused by mutations in genes encoding desmosomal proteins. These discoveries highlight the essential role of PERP in human desmosomes and epidermal homeostasis and further expand the heterogeneous spectrum of inherited keratinization disorders.

Phenotypic expansion of POFUT1 loss of function mutations in a disorder featuring segmental dyspigmentation with eczematous and folliculo-centric lesions. - Atzmony, Lihi; Zaki, Theodore D; Antaya, Richard J; Choate, Keith A (Am J Med Genet A, 2019)
Appearance of mosaic disorders in thin Blaschko lines suggests that somatic mutations in keratinocyte precursors underlie their pathogenesis. Germline heterozygous mutations in POFUT1 gene cause Dowling-Degos disease (DDD), a skin disease that features flexural reticulated hyperpigmentation and follicular-based lesions. POFUT1 mosaicism has not been described to date. Here, we describe a 9-year-old female with segmental hyper- and hypopigmented patches with overlying eczematous plaques and follicular papules. Employing paired whole exome sequencing of saliva and keratinocytes isolated from affected skin, we found a novel germline heterozygous POFUT1 deletion causing frameshift and premature codon termination and somatic copy-neutral loss of heterozygosity on chromosome 20 encompassing POFUT1. Expression levels of POFUT1 as well as other key regulators of the notch signaling pathway-NOTCH1, NOTCH2, and HES1-were reduced in affected keratinocytes compared with normal keratinocytes. Our findings provide the first evidence of POFUT1 postzygotic mutation and a phenotypic expansion of POFUT1 loss of function mutations. We show that a recessive loss of function mutation in POFUT1 produces a distinct clinical presentation with features (e.g., dermatitis) that are absent in the generalized form of DDD. This study demonstrates how analysis of mosaic disorders can reveal unexpected phenotypes for known genes.

CARD14-associated papulosquamous eruption: A spectrum including features of psoriasis and pityriasis rubra pilaris. - Craiglow, Brittany G; Boyden, Lynn M; Hu, Ronghua; Virtanen, Marie; Su, John; Rodriguez, Gabriela; McCarthy, Catherine; Luna, Paula; Larralde, Margarita; Humphrey, Stephen; Holland, Kristen E; Hogeling, Marcia; et al. (J Am Acad Dermatol, 2018)
BACKGROUND: Heterozygous mutations in caspase recruitment domain family member 14 gene (CARD14) have been shown to be associated with psoriasis and familial pityriasis rubra pilaris (PRP). Many subjects with CARD14 mutations display features of both disorders, which can result in diagnostic uncertainty. In addition, these eruptions are often recalcitrant to conventional psoriasis therapies such as methotrexate, oral retinoids, and tumor necrosis factor-α inhibitors. OBJECTIVE: We sought to describe the clinical characteristics, family history, and response to therapy in subjects with papulosquamous eruptions due to mutations in CARD14. METHODS: Subjects were referred for genetic testing as part of a registry of subjects with inherited disorders of keratinization. DNA was isolated from blood or saliva, and multiplex targeted sequencing or whole exome sequencing was performed. Clinical histories of subjects with CARD14 mutations were reviewed. RESULTS: We identified 15 kindreds with CARD14-associated papulosquamous eruption (CAPE). Characteristic features of CAPE include early age of onset; prominent involvement of the cheeks, chin, and ears; family history of psoriasis or PRP; minimal response to conventional topical and systemic psoriasis therapies; and improvement with ustekinumab. LIMITATIONS: Relatively small sample size. CONCLUSIONS: Many subjects with CARD14 mutations display characteristics of both psoriasis and PRP. We propose the term CARD14-associated papulosquamous eruption to describe this spectrum of disease. Subjects with clinical features suggestive of CAPE should undergo CARD14 sequencing and may benefit from treatment with ustekinumab.
Keywords: Age of Onset; CARD Signaling Adaptor Proteins; Child; Child, Preschool; Dermatologic Agents; Facial Dermatoses; Genetic Testing; Guanylate Cyclase; Humans; Infant; Infant, Newborn; Membrane Proteins; Phenotype; Pityriasis Rubra Pilaris; Psoriasis; Retreatment; Skin Diseases, Papulosquamous; Ustekinumab

Mutations in KDSR Cause Recessive Progressive Symmetric Erythrokeratoderma. - Boyden, Lynn M; Vincent, Nicholas G; Zhou, Jing; Hu, Ronghua; Craiglow, Brittany G; Bayliss, Susan J; Rosman, Ilana S; Lucky, Anne W; Diaz, Luis A; Goldsmith, Lowell A; Paller, Amy S; Lifton, Richard P; et al. (Am J Hum Genet, 2017)
The discovery of new genetic determinants of inherited skin disorders has been instrumental to the understanding of epidermal function, differentiation, and renewal. Here, we show that mutations in KDSR (3-ketodihydrosphingosine reductase), encoding an enzyme in the ceramide synthesis pathway, lead to a previously undescribed recessive Mendelian disorder in the progressive symmetric erythrokeratoderma spectrum. This disorder is characterized by severe lesions of thick scaly skin on the face and genitals and thickened, red, and scaly skin on the hands and feet. Although exome sequencing revealed several of the KDSR mutations, we employed genome sequencing to discover a pathogenic 346 kb inversion in multiple probands, and cDNA sequencing and a splicing assay established that two mutations, including a recurrent silent third base change, cause exon skipping. Immunohistochemistry and yeast complementation studies demonstrated that the mutations cause defects in KDSR function. Systemic isotretinoin therapy has achieved nearly complete resolution in the two probands in whom it has been applied, consistent with the effects of retinoic acid on alternative pathways for ceramide generation.
Keywords: Alcohol Oxidoreductases; Ceramides; Genes, Recessive; Genetic Complementation Test; Genetic Predisposition to Disease; Heterozygote; Humans; Intermediate Filament Proteins; Keratosis; Mutation; Polymorphism, Single Nucleotide; RNA Splicing; Saccharomyces cerevisiae

Cutaneous skeletal hypophosphatemia syndrome (CSHS) is a multilineage somatic mosaic RASopathy. - Lim, Young H; Ovejero, Diana; Derrick, Kristina M; Collins, Michael T; Choate, Keith A (J Am Acad Dermatol, 2016)
BACKGROUND: We recently demonstrated multilineage somatic mosaicism in cutaneous skeletal hypophosphatemia syndrome (CSHS), which features epidermal or melanocytic nevi, elevated fibroblast growth factor (FGF)-23, and hypophosphatemia, finding identical RAS mutations in affected skin and bone. OBJECTIVE: We sought to: (1) provide an updated overview of CSHS; (2) review its pathobiology; (3) present a new patient with CSHS; and (4) discuss treatment modalities. METHODS: We searched PubMed for "nevus AND rickets," and "nevus AND hypophosphatemia," identifying cases of nevi with hypophosphatemic rickets or elevated serum FGF-23. For our additional patient with CSHS, we performed histopathologic and radiographic surveys of skin and skeletal lesions, respectively. Sequencing was performed for HRAS, KRAS, and NRAS to determine causative mutations. RESULTS: Our new case harbored somatic activating HRAS p.G13 R mutation in affected tissue, consistent with previous findings. Although the mechanism of FGF-23 dysregulation is unknown in CSHS, interaction between FGF and MAPK pathways may provide insight into pathobiology. Anti-FGF-23 antibody KRN-23 may be useful in managing CSHS. LIMITATIONS: Multilineage RAS mutation in CSHS was recently identified; further studies on mechanism are unavailable. CONCLUSION: Patients with nevi in association with skeletal disease should be evaluated for serum phosphate and FGF-23. Further studies investigating the role of RAS in FGF-23 regulation are needed.
Keywords: Antibodies, Monoclonal; Antibodies, Monoclonal, Humanized; Fibroblast Growth Factor-23; Fibroblast Growth Factors; Genes, ras; Humans; Mosaicism; Nevus, Pigmented; Osteomalacia; Rickets, Hypophosphatemic; Skin Neoplasms; Syndrome

Dominant de novo DSP mutations cause erythrokeratodermia-cardiomyopathy syndrome. - Boyden, Lynn M; Kam, Chen Y; Hernández-Martín, Angela; Zhou, Jing; Craiglow, Brittany G; Sidbury, Robert; Mathes, Erin F; Maguiness, Sheilagh M; Crumrine, Debra A; Williams, Mary L; Hu, Ronghua; Lifton, Richard P; et al. (Hum Mol Genet, 2016)
Disorders of keratinization (DOK) show marked genotypic and phenotypic heterogeneity. In most cases, disease is primarily cutaneous, and further clinical evaluation is therefore rarely pursued. We have identified subjects with a novel DOK featuring erythrokeratodermia and initially-asymptomatic, progressive, potentially fatal cardiomyopathy, a finding not previously associated with erythrokeratodermia. We show that de novo missense mutations clustered tightly within a single spectrin repeat of DSP cause this novel cardio-cutaneous disorder, which we term erythrokeratodermia-cardiomyopathy (EKC) syndrome. We demonstrate that DSP mutations in our EKC syndrome subjects affect localization of desmosomal proteins and connexin 43 in the skin, and result in desmosome aggregation, widening of intercellular spaces, and lipid secretory defects. DSP encodes desmoplakin, a primary component of desmosomes, intercellular adhesion junctions most abundant in the epidermis and heart. Though mutations in DSP are known to cause other disorders, our cohort features the unique clinical finding of severe whole-body erythrokeratodermia, with distinct effects on localization of desmosomal proteins and connexin 43. These findings add a severe, previously undescribed syndrome featuring erythrokeratodermia and cardiomyopathy to the spectrum of disease caused by mutation in DSP, and identify a specific region of the protein critical to the pathobiology of EKC syndrome and to DSP function in the heart and skin.
Keywords: Amino Acid Sequence; Cardiomyopathies; Child; Child, Preschool; Connexin 43; Desmoplakins; Desmosomes; Female; Humans; Infant; Male; Molecular Sequence Data; Mutation, Missense; Myocardium; Protein Transport; Sequence Alignment; Skin; Skin Diseases, Genetic; Syndrome

GNA14 Somatic Mutation Causes Congenital and Sporadic Vascular Tumors by MAPK Activation. - Lim, Young H; Bacchiocchi, Antonella; Qiu, Jingyao; Straub, Robert; Bruckner, Anna; Bercovitch, Lionel; Narayan, Deepak; McNiff, Jennifer; Ko, Christine; Robinson-Bostom, Leslie; Antaya, Richard; Halaban, Ruth; et al. (Am J Hum Genet, 2016)
Vascular tumors are among the most common neoplasms in infants and children; 5%-10% of newborns present with or develop lesions within the first 3 months of life. Most are benign infantile hemangiomas that typically regress by 5 years of age; other vascular tumors include congenital tufted angiomas (TAs), kaposiform hemangioendotheliomas (KHEs), and childhood lobular capillary hemangiomas (LCHs). Some of these lesions can become locally invasive and unresponsive to pharmacologic intervention, leading to significant complications. Recent investigation has revealed that activating mutations in HRAS, KRAS, NRAS, GNAQ, and GNA11 can cause certain types of rare childhood vascular tumors, and we have now identified causal recurrent somatic activating mutations in GNA14 by whole-exome and targeted sequencing. We found somatic activating GNA14 c.614A>T (p.Gln205Leu) mutations in one KHE, one TA, and one LCH and a GNA11 c.547C>T (p.Arg183Cys) mutation in two LCH lesions. We examined mutation pathobiology via expression of mutant GNA14 or GNA11 in primary human endothelial cells and melanocytes. GNA14 and GNA11 mutations induced changes in cellular morphology and rendered cells growth-factor independent by upregulating the MAPK pathway. Our findings identify GNA14 mutations as a cause of childhood vascular tumors, offer insight into mechanisms of oncogenic transformation by mutations affecting Gaq family members, and identify potential targets for therapeutic intervention.
Keywords: Cells, Cultured; Child, Preschool; Enzyme Activation; GTP-Binding Protein alpha Subunits; GTP-Binding Protein alpha Subunits, Gq-G11; Human Umbilical Vein Endothelial Cells; Humans; Infant; Infant, Newborn; Intercellular Signaling Peptides and Proteins; Male; MAP Kinase Signaling System; Melanocytes; Mitogen-Activated Protein Kinases; Mutation; Proto-Oncogene Proteins c-akt; Vascular Neoplasms

Keratoacanthoma Shares Driver Mutations with Cutaneous Squamous Cell Carcinoma. - Lim, Young H; Fisher, Jonathan M; Bosenberg, Marcus W; Choate, Keith A; Ko, Christine J (J Invest Dermatol, 2016)
Keywords: Aged; Aged, 80 and over; Biomarkers, Tumor; Biopsy; Carcinoma, Squamous Cell; Cohort Studies; Diagnosis, Differential; Exome; Female; Humans; Keratoacanthoma; Loss of Heterozygosity; Male; Middle Aged; Mutation; Polymorphism, Single Nucleotide; Skin; Skin Neoplasms; Whole Exome Sequencing

Somatic Mutations in NEK9 Cause Nevus Comedonicus. - Levinsohn, Jonathan L; Sugarman, Jeffrey L; McNiff, Jennifer M; Antaya, Richard J; Choate, Keith A (Am J Hum Genet, 2016)
Acne vulgaris (AV) affects most adolescents, and of those affected, moderate to severe disease occurs in 20%. Comedones, follicular plugs consisting of desquamated keratinocytes and sebum, are central to its pathogenesis. Despite high heritability in first-degree relatives, AV genetic determinants remain incompletely understood. We therefore employed whole-exome sequencing (WES) in nevus comedonicus (NC), a rare disorder that features comedones and inflammatory acne cysts in localized, linear configurations. WES identified somatic NEK9 mutations, each affecting highly conserved residues within its kinase or RCC1 domains, in affected tissue of three out of three NC-affected subjects. All mutations are gain of function, resulting in increased phosphorylation at Thr210, a hallmark of NEK9 kinase activation. We found that comedo formation in NC is marked by loss of follicular differentiation markers, expansion of keratin-15-positive cells from localization within the bulge to the entire sub-bulge follicle and cyst, and ectopic expression of keratin 10, a marker of interfollicular differentiation not present in normal follicles. These findings suggest that NEK9 mutations in NC disrupt normal follicular differentiation and identify NEK9 as a potential regulator of follicular homeostasis.
Keywords: Adolescent; Adult; Child; Female; Fluorescent Antibody Technique; High-Throughput Nucleotide Sequencing; Humans; Male; Mutation; Nevus; NIMA-Related Kinases; Prognosis; Skin Neoplasms; Young Adult

Dominant De Novo Mutations in GJA1 Cause Erythrokeratodermia Variabilis et Progressiva, without Features of Oculodentodigital Dysplasia. - Boyden, Lynn M; Craiglow, Brittany G; Zhou, Jing; Hu, Ronghua; Loring, Erin C; Morel, Kimberly D; Lauren, Christine T; Lifton, Richard P; Bilguvar, Kaya; Paller, Amy S; Choate, Keith A (J Invest Dermatol, 2015)
Genetic investigation of inherited skin disorders has informed the understanding of skin self-renewal, differentiation, and barrier function. Erythrokeratodermia variabilis et progressiva (EKVP) is a rare, inherited skin disease that is characterized by transient figurate patches of erythema, localized or generalized scaling, and frequent palmoplantar keratoderma. By using exome sequencing, we show that de novo missense mutations in GJA1 (gap junction protein alpha 1) cause EKVP. The severe, progressive skin disease in EKVP subjects with GJA1 mutations is distinct from limited cutaneous findings rarely found in the systemic disorder oculodentodigital dysplasia, also caused by dominant GJA1 mutations. GJA1 encodes connexin 43 (Cx43), the most widely expressed gap junction protein. We show that the GJA1 mutations in EKVP subjects lead to disruption of Cx43 membrane localization and aggregation within the Golgi. These findings reveal a critical role for Cx43 in epidermal homeostasis, and they provide evidence of organ-specific pathobiology resulting from different mutations within GJA1.
Keywords: Amino Acid Sequence; Cell Membrane; Child; Child, Preschool; Connexin 43; Connexins; Craniofacial Abnormalities; Disease Progression; Erythrokeratodermia Variabilis; Exome; Eye Abnormalities; Female; Foot Deformities, Congenital; Golgi Apparatus; HeLa Cells; Humans; Immunohistochemistry; Male; Molecular Sequence Data; Mutagenesis, Site-Directed; Mutation; Phenotype; Sequence Analysis, DNA; Sequence Homology, Amino Acid; Skin Diseases; Syndactyly; Tooth Abnormalities

Frequent somatic reversion of KRT1 mutations in ichthyosis with confetti. - Choate, Keith A; Lu, Yin; Zhou, Jing; Elias, Peter M; Zaidi, Samir; Paller, Amy S; Farhi, Anita; Nelson-Williams, Carol; Crumrine, Debra; Milstone, Leonard M; Lifton, Richard P (J Clin Invest, 2015)
Widespread reversion of genetic disease is rare; however, such events are particularly evident in some skin disorders in which normal clones develop on a background of affected skin. We previously demonstrated that mutations in keratin 10 (KRT10) cause ichthyosis with confetti (IWC), a severe dominant disorder that is characterized by progressive development of hundreds of normal skin spots via revertant mosaicism. Here, we report on a clinical and histological IWC subtype in which affected subjects have red, scaly skin at birth, experience worsening palmoplantar keratoderma in childhood, and develop hundreds of normal skin spots, beginning at around 20 years of age, that increase in size and number over time. We identified a causal de novo mutation in keratin 1 (KRT1). Similar to IWC-causing KRT10 mutations, this mutation in KRT1 resulted in a C-terminal frameshift, replacing 22 C-terminal amino acids with an alternate 30-residue peptide. Mutant KRT1 caused partial collapse of the cytoplasmic intermediate filament network and mislocalized to the nucleus. As with KRT10 mutations causing IWC, reversion of KRT1 mutations occurred via mitotic recombination. Because reversion is not observed with other disease-causing keratin mutations, the results of this study implicate KRT1 and KRT10 C-terminal frameshift mutations in the high frequency of revertant mosaicism in IWC.
Keywords: Adult; Age of Onset; Amino Acid Sequence; Cell Line, Tumor; Cell Nucleus; Child; Child, Preschool; Chromosomes, Human, Pair 12; Cytoskeleton; Frameshift Mutation; Humans; Ichthyosis; Intermediate Filaments; Keratin-1; Keratinocytes; Loss of Heterozygosity; Male; Molecular Sequence Data; Mosaicism; Phenotype; Polymorphism, Single Nucleotide; Protein Transport; Transfection

Somatic Activating RAS Mutations Cause Vascular Tumors Including Pyogenic Granuloma. - Lim, Young H; Douglas, Stephanie R; Ko, Christine J; Antaya, Richard J; McNiff, Jennifer M; Zhou, Jing; Choate, Keith A; Narayan, Deepak (J Invest Dermatol, 2015)
Keywords: Adolescent; Cell Proliferation; Child; Child, Preschool; Female; Gene Expression Regulation, Neoplastic; Granuloma, Pyogenic; Humans; Infant; Infant, Newborn; Male; Mutation; ras Proteins; Vascular Neoplasms

Somatic p.T771R KDR (VEGFR2) Mutation Arising in a Sporadic Angioma During Ramucirumab Therapy. - Lim, Young H; Odell, Ian D; Ko, Christine J; Choate, Keith A (JAMA Dermatol, 2015)
IMPORTANCE: Inhibition of angiogenesis is an effective anticancer strategy because neoplasms require a rich blood supply. Ramucirumab, approved by the US Food and Drug Administration in 2014 to treat gastric adenocarcinomas and non-small cell lung carcinomas, targets vascular endothelial growth factor 2 (VEGFR2). We identified a patient prescribed a regimen of irinotecan hydrochloride, cetuximab, and ramucirumab for metastatic rectal cancer (diagnosed in November 2013 and treated through early January 2015) who developed a new-onset, expanding vascular lesion on his right leg. Via exome sequencing, we found that the lesion contained a single somatic mutation in KDR (encodes VEGFR2), possibly in response to ramucirumab. Vascular tumors are not a known complication of antiangiogenic therapeutics. OBSERVATIONS: Exome sequencing of the well-demarcated, blanching vascular lesion on the lateral right shin revealed a somatic p.T771R mutation in KDR, without evidence of other somatic mutations or loss of heterozygosity. Histological features included lobules of small vessels within the dermis, resembling a tufted angioma. CONCLUSIONS AND RELEVANCE: A potential adverse effect of ramucirumab in combination therapy is the development of sporadic angiomas. The p.T771R mutation was previously implicated in autophosphorylation of VEGFR2 and reported in angiosarcomas alongside other driver mutations. Our observations suggest that this mutation confers a proliferative advantage in the setting of ramucirumab therapy. Patients receiving ramucirumab should be monitored for the development of new vascular lesions.
Keywords: Adult; Angiogenesis Inhibitors; Antibodies, Monoclonal; Antineoplastic Combined Chemotherapy Protocols; Camptothecin; Cetuximab; Hemangioma; Humans; Irinotecan; Male; Mutation; Rectal Neoplasms; Skin Neoplasms; Vascular Endothelial Growth Factor Receptor-2

Somatic V600E BRAF Mutation in Linear and Sporadic Syringocystadenoma Papilliferum. - Levinsohn, Jonathan L; Sugarman, Jeffrey L; Bilguvar, Kaya; McNiff, Jennifer M; Choate, Keith A (J Invest Dermatol, 2015)
Keywords: Biopsy, Needle; Child; Cystadenoma; Female; Gene Expression Regulation, Neoplastic; Humans; Immunohistochemistry; Mutation; Proto-Oncogene Proteins B-raf; Sweat Gland Neoplasms; Syringoma

Multilineage somatic activating mutations in HRAS and NRAS cause mosaic cutaneous and skeletal lesions, elevated FGF23 and hypophosphatemia. - Lim, Young H; Ovejero, Diana; Sugarman, Jeffrey S; Deklotz, Cynthia M C; Maruri, Ann; Eichenfield, Lawrence F; Kelley, Patrick K; Jüppner, Harald; Gottschalk, Michael; Tifft, Cynthia J; Gafni, Rachel I; Boyce, Alison M; et al. (Hum Mol Genet, 2014)
Pathologically elevated serum levels of fibroblast growth factor-23 (FGF23), a bone-derived hormone that regulates phosphorus homeostasis, result in renal phosphate wasting and lead to rickets or osteomalacia. Rarely, elevated serum FGF23 levels are found in association with mosaic cutaneous disorders that affect large proportions of the skin and appear in patterns corresponding to the migration of ectodermal progenitors. The cause and source of elevated serum FGF23 is unknown. In those conditions, such as epidermal and large congenital melanocytic nevi, skin lesions are variably associated with other abnormalities in the eye, brain and vasculature. The wide distribution of involved tissues and the appearance of multiple segmental skin and bone lesions suggest that these conditions result from early embryonic somatic mutations. We report five such cases with elevated serum FGF23 and bone lesions, four with large epidermal nevi and one with a giant congenital melanocytic nevus. Exome sequencing of blood and affected skin tissue identified somatic activating mutations of HRAS or NRAS in each case without recurrent secondary mutation, and we further found that the same mutation is present in dysplastic bone. Our finding of somatic activating RAS mutation in bone, the endogenous source of FGF23, provides the first evidence that elevated serum FGF23 levels, hypophosphatemia and osteomalacia are associated with pathologic Ras activation and may provide insight in the heretofore limited understanding of the regulation of FGF23.
Keywords: Adolescent; Child; Exome; Female; Fibroblast Growth Factors; Gene Expression Regulation, Developmental; GTP Phosphohydrolases; Humans; Hypophosphatemia; Male; Membrane Proteins; Mutation; Nevus; Nevus, Pigmented; Osteomalacia; Proto-Oncogene Proteins p21(ras); Sequence Analysis, DNA; Skin; Skin Neoplasms

Somatic HRAS p.G12S mutation causes woolly hair and epidermal nevi. - Levinsohn, Jonathan L; Teng, Joyce; Craiglow, Brittany G; Loring, Erin C; Burrow, T Andrew; Mane, Shrikant S; Overton, John D; Lifton, Richard P; McNiff, Jennifer M; Lucky, Anne W; Choate, Keith A (J Invest Dermatol, 2014)
Keywords: Adherens Junctions; Child; Exome; Female; Genes, ras; Hair; Hair Diseases; Hair Follicle; Humans; Intermediate Filaments; Mosaicism; Mutation; Nevus; Phenotype; ras Proteins; Sequence Analysis, DNA; Signal Transduction

Whole-exome sequencing reveals somatic mutations in HRAS and KRAS, which cause nevus sebaceus. - Levinsohn, Jonathan L; Tian, Li C; Boyden, Lynn M; McNiff, Jennifer M; Narayan, Deepak; Loring, Erin S; Yun, Duri; Sugarman, Jeffrey L; Overton, John D; Mane, Shrikant M; Lifton, Richard P; Paller, Amy S; et al. (J Invest Dermatol, 2013)
Keywords: Adolescent; Adult; Amino Acid Sequence; Biopsy; Child; Child, Preschool; Cohort Studies; Epidermis; Exome; Humans; Infant; Middle Aged; Molecular Sequence Data; Mutation; Nevus, Sebaceous of Jadassohn; Proto-Oncogene Proteins; Proto-Oncogene Proteins p21(ras); ras Proteins; Sequence Analysis, DNA; Young Adult